Bhineka Tunggal Ika Village: Patterns of Religious and Cultural Relations in a Local Wisdom-Based Multireligious Society - Huda, Ulul; Asyik, Noor; Sugiarti, Iis (Jurnal Fuaduna : Jurnal Kajian Keagamaan dan Kemasyarakatan, 2022)
This article aims to find a pattern of relations between religion and culture in Banjarpanepen Village as a miniature portrait of Bhineka Tunggal Ika Village, which upholds mutual respect and tolerance in social and religious life. In the village, there are Muslims, Christians, Buddhists, and Indigenous Religion (Penghayat) who can live in harmony supported by the local cultural locality. This type of research is qualitative with an ethnographic approach and uses observation, interviews and documentation. Key informants were determined through purposive sampling, including the village, traditional, religious, and community leaders. The data obtained were then analyzed descriptively-analytically to reveal the facts that occurred theoretically and empirically related to the research focus. The results of this study indicate: (1) a portrait of the community's diversity, which includes religion, culture, and natural potential. In this case, the philosophy of cultural locality is used as the basis for every community social activity. (2) Community communication patterns include social relations, cultural customs and religion. Finally, (3) the strategy to realize Bhineka Tunggal Ika Village is to strengthen the role of religious leaders, strengthen the tradition of cooperation, make local wisdom a cultural strategy in realizing tolerance and develop a tourism village based on local wisdom.